Exploring Translingual Practices as a Pathway to Inclusive Language Acquisitio - Amiena Peck; Quentin Williams (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study examines how translingual practices function as a pathway to inclusive language acquisition and investigates their influence on language proficiency, student engagement, and classroom inclusivity in multilingual educational settings. Subjects and Methods: A convergent mixed-methods design was employed involving 150 students and 10 English language teachers from five multilingual secondary schools in the Western Cape Province, South Africa, during 2024. Data were collected through classroom observations, questionnaires, interviews, focus group discussions, and language proficiency tests. Quantitative data were analyzed using descriptive statistics, Pearson correlation, independent samples t-tests, and regression analysis, while qualitative data were examined through thematic analysis. Results: Students exposed to higher levels of translingual practices demonstrated significantly greater improvements in English proficiency than those in low exposure classrooms. Translingual practices showed significant positive relationships with language proficiency, student engagement, and classroom inclusivity, with language proficiency emerging as the strongest predicted outcome (β = 0.52). Qualitative findings revealed that multilingual interaction reduced cognitive barriers, increased learner confidence, strengthened participation, and fostered a stronger sense of belonging. However, teachers identified limited instructional time, inadequate professional preparation, curriculum constraints, and insufficient institutional support as major implementation challenges. Conclusions: Translingual pedagogy provides an effective and sustainable framework for inclusive language learning by integrating cognitive, social, and linguistic development. Its long-term success requires supportive institutional policies, curriculum flexibility, multilingual assessment, and continuous teacher professional development.